FOOD AND FEEDING OF LIZARD FISHES (SAURIDA SPP.) FROM NORTH WESTERN PART OF BAY OF BENGAL - Rao, K Venkata Subba (Indian Journal of Fisheries, 2011)
The food and feeding of Saurida turnbil was studied with reference to size of fish, time (seasonal and diurnal), regions (latitude zones), sex and maturity. Though there was not much difference in the composition of the food in respect of the above factors, variations were however, 6bserved in the intensity of feeding. Fish formed the single major component <70 to 80%) of the food. The feeding intensity was low during the spawning period. Two peaks, one in the morning and the other in the noon, were observed in the feeding intensities according to time of day. The maturing fish bad the highest feeding intensity. The values of Ivlev’s index of electivity (E) for Letognathus blttdus were positive for 6 months and negative for 4 months. The results1 of studiesi on the food and feeding of S. undosquomis and S. longimarms are more or less similar